Bipolar membrane electrodialysis membrane stack and use method thereof
By using the combined technology of perfluorosulfonated polyvinyl chloride, quaternary ammonized polyethylene and modified graphene in the bipolar membrane electrodialysis membrane stack, combined with the regulation of feed liquid and pressure, the performance and use of bipolar membranes are solved. The problem of life span has achieved a bipolar membrane with high ion exchange capacity, low transmembrane voltage and acid-base resistance, extending the service life and reducing the occurrence of side reactions.
Patent Information
- Application Number
- CN202411372508.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The performance and service life of existing bipolar membranes need to be further improved, especially in the construction of internal hydrolytic layer and unilateral modification, resulting in reduced performance and short service life.
Using bipolar membrane electrodialysis membrane stacks, including cation exchange membranes, anion exchange membranes and hydrolyzed functional layers, are prepared by perfluorosulfonated polyvinyl chloride, quaternary ammonized polyethylene and modified graphene, combined with electrostatic textile and thermal pressing technology , form a high-performance bipolar membrane, and optimize the electrodialysis process by regulating the feed liquid composition and pressure, as well as real-time detection and adjustment of the membrane stack current.
It significantly improves the ion exchange capacity, blasting strength, acid and alkali resistance and service life of the bipolar membrane, reduces the risk of transmembrane voltage and swelling, extends the service life of the membrane, and reduces the voltage and current mismatch caused by Side reactions protect the membrane structure.
Smart Images

Figure CN119236684A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of bipolar membrane processing and maintenance, and in particular to a bipolar membrane electrodialysis membrane stack and a use method thereof. Background Art
[0002] With the development of science and technology, the development of a new generation of bipolar membrane materials has enhanced the chemical corrosion resistance and mechanical stability of the membrane, significantly extended its service life, and through process optimization, such as feed liquid pretreatment, fine control of operating conditions (including optimization of flow rate, pressure and temperature) and pollutant monitoring, the mechanical and chemical burden of the membrane is reduced, thereby further extending its service life.
[0003] Prior art CN109012201A discloses an electrodialyser, comprising an anode plate, a membrane stack, a cathode plate and a compression plate for fixing and sealing the membrane stack; the membrane stack comprises a first membrane pair and a second membrane pair; wherein the first membrane pair and the second membrane pair are arranged alternately; the first membrane pair is arranged in the following manner: partition-first anion exchange membrane-partition-first cation exchange membrane; the second membrane pair is arranged in the following manner: partition-second anion exchange membrane-partition-second cation exchange membrane; a monovalent selective cation exchange membrane is also installed between the first membrane pair adjacent to the anode plate and the anode plate; in combination with the cation exchange membrane, each group of the first membrane pair and the second membrane pair in the same group has four compartments, the four compartments are respectively provided with separate water flow channels, and each compartment is connected to a corresponding feed water tank and a production water tank through a corresponding water flow channel; the invention can separate and reorganize ions that are prone to scaling, reduce scaling, and increase the service life of the equipment.
[0004] Prior art CN112546873A discloses a bipolar membrane and a preparation method thereof. The bipolar membrane has a cation exchange membrane and an anion exchange membrane. The base membrane is prepared by copolymerizing 4-vinylbenzyl glycidyl ether with divinylbenzene. Then, the ring-opening reaction of the epoxy groups in the base membrane is used to introduce sulfonic acid groups and quaternary ammonium groups on both sides of the membrane to prepare the bipolar membrane. The bipolar membrane is not prone to bubbling and stratification during use, and has better mechanical strength and chemical stability. The bipolar membrane preparation method has mild reaction conditions and a relatively simple manufacturing process.
[0005] The anion and cation exchange membrane is prepared by preparing a base membrane and introducing functional functional groups through a ring-opening reaction. However, the modification is performed on only two sides of a bipolar membrane, without considering the construction of the hydrolysis layer inside the bipolar membrane, which reduces the practicality of the bipolar membrane prepared by this invention. In addition, in the process of modifying one side, it is difficult to ensure that the opposite side is not modified, which will lead to reduced performance and service life of the prepared bipolar membrane.
[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0007] The object of the present invention is to provide a bipolar membrane electrodialysis membrane stack and a method of using the same, so as to solve the technical problem in the prior art that the performance and service life of the bipolar membrane need to be further improved.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A bipolar membrane electrodialysis membrane stack, comprising an anode plate, a plurality of membrane stack units, a cathode plate and a pressing plate for fixing the membrane stack, wherein the membrane stack unit is sequentially provided with a cation exchange membrane, a bipolar membrane and an anion exchange membrane;
[0010] The bipolar membrane includes a cation exchange membrane, an anion exchange membrane and a hydrolysis functional layer;
[0011] The cation exchange membrane is prepared from perfluorosulfonated polyvinyl chloride, the anion exchange membrane is prepared from quaternized polyethylene, and the hydrolysis functional layer is composed of a modified hydrolysis aid prepared from modified graphene.
[0012] Further, the preparation method of perfluorosulfonated polyvinyl chloride comprises the following steps:
[0013] A1. Add polyvinyl chloride powder, 20-30wt% potassium peroxide solution and ethanol into a reactor and stir. Raise the temperature of the reactor to 60-80°C, keep stirring for 1-2h, and perform post-treatment to obtain activated polyvinyl chloride.
[0014] The synthetic reaction equation of activated polyvinyl chloride is:
[0015]
[0016] The synthetic reaction principle of activated polyvinyl chloride is as follows: the polyvinyl chloride chain segments are activated by alkaline solution potassium peroxide, and the hydroxyl groups on the ethanol replace the chlorine groups on the polyvinyl chloride chain segments, and finally the activated polyvinyl chloride is prepared.
[0017] A2, adding activated polyvinyl chloride, 3-aminopropyltriethoxysilane, triethylamine, N,N-dimethylformamide and deionized water into a reaction kettle, stirring at room temperature for 1-2 hours, and post-treating to obtain aminated polyvinyl chloride;
[0018] The synthetic reaction equation of ammoniated polyvinyl chloride is:
[0019]
[0020] Where:
[0021] The synthesis principle of ammoniated polyvinyl chloride is as follows: under the catalysis of alkaline conditions provided by triethylamine, the siloxane on 3-aminopropyltriethoxysilane is hydrolyzed to produce silanol, which reacts with the hydroxyl groups on the activated polyvinyl chloride chain segments, introducing amino groups on the polyvinyl chloride chain segments, and finally preparing ammoniated polyvinyl chloride.
[0022] A3. Add ammoniated polyvinyl chloride, perfluorooctane sulfonyl fluoride, N,N-dimethylformamide and cyclohexane into a reaction kettle and stir. The temperature of the reaction kettle is increased to 40-60°C. The reaction is kept warm for 2-3 hours. After post-treatment, perfluorosulfonated polyvinyl chloride is obtained.
[0023] The synthetic reaction equation of perfluorosulfonated polyvinyl chloride is:
[0024]
[0025] Where:
[0026] The synthesis reaction equation of perfluorosulfonated polyvinyl chloride is: under heating conditions, the sulfonyl group on perfluorooctanesulfonyl fluoride reacts with the amino group on the aminated polyvinyl chloride to vulcanize the polyvinyl chloride chain segments, and finally prepare perfluorosulfonated polyvinyl chloride.
[0027] Furthermore, in step A1, the stirring rate is 120 rpm, and the amount ratio of polyvinyl chloride powder, 20-30 wt% potassium peroxide solution and ethanol is 1-3 g: 2-3 mL: 1-2 mL; in step A2, the stirring rate is 120 rpm, and the amount ratio of activated polyvinyl chloride, 3-aminopropyltriethoxysilane, triethylamine, N,N-dimethylformamide and deionized water is 6-9 g: 2-3 g: 0.3-0.5 g: 16-20 mL: 12-15 mL; in step A3, the stirring rate is 120 rpm, and the amount ratio of aminated polyvinyl chloride, perfluorooctane sulfonyl fluoride, N,N-dimethylformamide and cyclohexane is 6-9 g: 2-3 g: 16-20 mL: 12-15 mL.
[0028] Furthermore, in step A1, the post-treatment includes: after the temperature of the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain activated polyvinyl chloride; in step A2, the post-treatment includes: after the temperature of the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain ammoniated polyvinyl chloride; in step A3, the post-treatment includes: after the temperature of the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain perfluorosulfonated polyvinyl chloride.
[0029] Further, the preparation method of quaternized polyethylene comprises the following steps:
[0030] B1. Add N,N,N',N'-tetramethyl-2-butene-1,4-diamine, isocyanoethyl methacrylate, vinylbenzene, azobisisobutyronitrile and N,N-dimethylformamide into a reaction kettle and stir. The temperature of the reaction kettle is raised to 40-60°C, and the mixture is stirred for 1-2 hours at the same temperature. The modified polyethylene is obtained by post-treatment.
[0031] The synthetic reaction equation of modified polyethylene is:
[0032]
[0033] Where:
[0034] The synthesis principle of modified polyethylene is as follows: under the catalysis of free radical initiator azobisisobutyronitrile, N,N,N',N'-tetramethyl-2-butene-1,4-diamine, isocyanoethyl methacrylate and vinylbenzene undergo free radical polymerization reaction to finally prepare modified polyethylene.
[0035] B2. Add modified polypropylene, triethylamine and N,N-dimethylformamide into a reactor and stir. The temperature of the reactor is raised to 30-50°C and the stirring rate is 150-180rpm. Methyl chloride is added dropwise during stirring. The dropping operation is maintained for 1-3h. After the dropping is completed, the stirring rate is reduced to 60-80rpm. The reaction is kept warm for 1-2h and the quaternized polyethylene is obtained by post-treatment.
[0036] The synthetic reaction equation of quaternary ammoniated polyethylene is:
[0037]
[0038] Where:
[0039] The synthetic reaction principle of quaternized polyethylene is as follows: under the catalysis of triethylamine, methyl chloride continuously reacts with the tertiary amino group on the modified polyethylene during the dripping process, and finally a quaternary ammonium salt is prepared.
[0040] Further, in step B1, the stirring rate is 60-80rpm, and the amount ratio of N,N,N',N'-tetramethyl-2-butene-1,4-diamine, isocyanoethyl methacrylate, vinylbenzene, azobisisobutyronitrile and N,N-dimethylformamide is 5-8g:3-5g:2-3g:0.8-1.2g:40-50mL; in step B2, the amount ratio of modified polypropylene, triethylamine, N,N-dimethylformamide and methyl chloride is 2-3g:0.1-0.3g:12-18mL:0.3-0.5g.
[0041] Furthermore, in step B1, the post-treatment includes: after the temperature of the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and distilled under reduced pressure until no liquid is produced to obtain modified polyethylene; in step B2, the post-treatment includes: after the temperature of the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 50°C, and distilled under reduced pressure until no liquid is produced to obtain quaternized polyethylene.
[0042] Furthermore, the preparation method of the modified hydrolysis aid comprises the following steps:
[0043] C1, adding nano titanium dioxide particles and 20-30wt% sodium hydroxide aqueous solution into a reaction kettle for ultrasonication, raising the temperature of the reaction kettle to 60-80°C, maintaining the temperature for 1-2h, and post-treating to obtain modified nano titanium dioxide particles;
[0044] C2, adding multilayer graphene and ethanol to a reactor and stirring, stirring at room temperature for 15-20 minutes, pouring the acidified solution into the reactor, and raising the temperature of the reactor to 40-60°C, after acidification for 0.5 hours, adding an oxidant to the reactor, keeping warm and stirring for 8-12 hours, and post-treating to obtain graphene oxide;
[0045] C3. The modified nano titanium dioxide particles, triethylamine and ethanol are mixed evenly and added into an atomizer. After atomization operation, the generated gas is evenly sprayed on the surface of graphene oxide, and a modified hydrolysis aid is obtained by post-treatment.
[0046] The synthetic reaction principle of the modified hydrolysis aid is as follows: during the process of heating and ultrasonic treatment of nano-titanium dioxide particles in an alkaline solution, the hydroxide provided by sodium hydroxide continuously bonds with the titanium atoms on the surface of the nano-titanium dioxide, introducing a large number of hydroxyl groups on its surface, and then spraying it on the surface of graphene oxide after atomization. The graphene oxide is acidified by an acidification solution and finally oxidized by an oxidant. The oxidized graphene surface has active groups such as hydroxyl groups, carboxyl groups and epoxy groups. Under the catalysis of triethylamine, the hydroxyl groups on the surface of the modified nano-titanium dioxide particles react with the active groups on the surface of the graphene oxide to form a tight structure connected by chemical bonds. Finally, the modified titanium dioxide particles are evenly dispersed on the surface of the graphene oxide and in the internal void structure, and finally the modified hydrolysis aid is prepared.
[0047] Furthermore, in step C1, the ultrasonic frequency is 20-40kHz, and the dosage ratio of nano-titanium dioxide particles and 20-30wt% sodium hydroxide aqueous solution is 3-5g:10-15mL; in step C2, the dosage ratio of multilayer graphene, ethanol, acidified solution and oxidant is 5-8g:18-24mL:10-12mL:3-5g, the acidified solution is prepared by a volume ratio of 5:1 of concentrated sulfuric acid and concentrated nitric acid, and the oxidant is prepared by a mass ratio of 2:1 of potassium permanganate and sodium persulfate; in step C3, the stirring rate is 60-80rpm, and the dosage ratio of modified nano-titanium dioxide particles, triethylamine, ethanol and graphene oxide is 3-5g:0.3-0.5g:18-24mL:8-10g.
[0048] Furthermore, in step C1, post-processing includes: after the ultrasonic treatment is completed, placing the material in a drying oven at a temperature of 80°C for vacuum drying until the material reaches a constant weight, thereby obtaining modified nano titanium dioxide particles; in step C2, post-processing includes: after the reaction is completed, placing the material in a drying oven at a temperature of 80°C for vacuum drying until the material reaches a constant weight, thereby obtaining modified nano titanium dioxide particles; in step C3, post-processing includes: after the spraying is completed, placing the material in a drying oven at a temperature of 80°C for vacuum drying until the material reaches a constant weight, thereby obtaining a modified hydrolysis aid.
[0049] Further, the preparation method of the bipolar membrane is:
[0050] D1. Add perfluorosulfonated polyvinyl chloride, modified nano titanium dioxide particles and N,N-dimethylformamide into a reactor, mix well and then add into an electrostatic spinning machine, set the voltage of the electrostatic spinning machine to 20-25 kV, set the spinning distance to 20-30 cm, control the flow rate to 0.5-1 L / h, and the spinning thickness to 50-100 μm, and post-treat to obtain a cation exchange membrane;
[0051] D2, adding quaternized polyethylene, modified nano titanium dioxide particles and N,N-dimethylformamide to the reactor, mixing evenly, and then adding to the electrostatic spinning machine, setting the voltage of the electrostatic spinning machine to 20-25 kV, the spinning distance to 20-30 cm, the flow rate to 0.5-1 L / h, the spinning thickness to 50-100 μm, and post-processing to obtain an anion exchange membrane;
[0052] D3. Disperse the modified hydrolysis aid in a 1-3wt% triethylamine aqueous solution to obtain a dispersion, use a spin coater to spin-coat the dispersion on one side of the anion exchange membrane, control the spin coating thickness to 25-50μm, then attach the cation exchange membrane to the side of the anion exchange membrane spin-coated with the dispersion, use a hot press to extrude the material, control the pressure of the hot press to 5-8MPa, the temperature to 40-60°C, extrude for 5-10min, and post-treat to obtain a bipolar membrane.
[0053] The synthesis reaction principle of the bipolar membrane is as follows: the active groups on the surface of the modified hydrolysis aid react with the active groups such as hydroxyl groups on the surface of the cation exchange membrane and the anion exchange membrane under the catalysis of triethylamine, and finally form a stable structure connected by chemical bonds, and the bipolar membrane is obtained after curing.
[0054] Furthermore, in step D1, the dosage ratio of perfluorosulfonated polyvinyl chloride, modified nano titanium dioxide particles and N,N-dimethylformamide is 3-5g:0.3-0.5g:18-25mL; in step D2, the dosage ratio of quaternized polyethylene, modified nano titanium dioxide particles and N,N-dimethylformamide is 3-5g:0.3-0.5g:18-25mL; in step D3, the dosage ratio of modified hydrolysis aid dispersed in 1-3wt% triethylamine aqueous solution is 3-5g:20-30mL.
[0055] Furthermore, in step D1, post-treatment includes: after the electrospinning is completed, the material is placed in a drying oven at a temperature of 80°C for vacuum drying until the material has a constant weight, thereby obtaining a cation exchange membrane; in step D2, post-treatment includes: after the electrospinning is completed, the material is placed in a drying oven at a temperature of 50°C for vacuum drying until the material has a constant weight, thereby obtaining an anion exchange layer; in step D3, post-treatment includes: after the electrospinning is completed, the material is placed in a drying oven at a temperature of 50°C for vacuum drying until the material has a constant weight, thereby obtaining a bipolar membrane.
[0056] A method for using a bipolar membrane electrodialysis membrane stack, comprising the following method:
[0057] S1. After assembling the bipolar membrane into a membrane stack unit, the membrane stack unit is installed in an electrodialysis device, and a sensor is installed in the electrodialysis device;
[0058] S2. Treat the liquid composition before feeding the electrodialysis device to control the Ca content in the liquid 2+ Mg 2+ and Zn 2+ The concentration of divalent metal ions is less than 0.5 g / L;
[0059] S3, stabilize the feed pressure during feeding, and maintain the feed pressure between 0.06-0.09MPa;
[0060] S4. Adjust the membrane stack current during the electrolysis process and detect the membrane stack voltage during the electrolysis process. When the voltage is abnormal, temporarily reduce the operating current of the membrane stack corresponding to the abnormal voltage to 10-50A, observe the voltage change trend, and gradually restore the original operating current when the voltage stabilizes.
[0061] The present invention has the following beneficial effects:
[0062] 1. Through the use method of a bipolar membrane electrodialysis membrane stack provided by the present invention, the regulation of the feed liquid composition reduces the adhesion of divalent ions to the membrane surface, slows down the process of membrane blockage and calcification, and greatly improves the life of the membrane; regulates the pressure of the feed liquid to reduce the negative impact of membrane stack diaphragm bulging caused by excessive feed liquid pressure, thereby reducing the occurrence of leakage, and at the same time, it will not cause insufficient feed due to too low pressure, thereby causing pressure imbalance in the acid-base salt chamber, and membrane burning due to lack of material; real-time detection of the membrane stack voltage and adjustment of the bipolar membrane operating current reduce the reduction of ion separation efficiency in the bipolar membrane caused by voltage and current mismatch, resulting in ion accumulation or initiation of side reactions, such as gas precipitation on the electrode surface, reduce the adverse effects of such side reactions on the material and performance of the membrane, protect the membrane structure, and delay the degradation of the membrane material. At the same time, the bipolar membrane is very sensitive to the transmembrane voltage (membrane stack voltage). When the voltage is abnormal, it will cause local overheating, mechanical damage and chemical degradation of the membrane, thereby reducing the service life of the membrane.
[0063] 2. In the process of preparing a bipolar membrane, the present invention first prepares a cation exchange membrane that effectively attracts cations and transmits positively charged ions through the membrane through a large number of sulfonic acid groups on its surface, and prepares an anion exchange membrane that effectively attracts and transmits positively charged ions through the membrane through a large number of quaternary ammonium salt groups on its surface, thereby improving the ion exchange capacity of the bipolar membrane and reducing the transmembrane voltage. The large number of fluorine groups and tertiary amine structures respectively present in the molecular chains further improve the acid and alkali resistance and anti-swelling performance of the two. The modified nano-silica particles inside the two provide a skeleton structure for the membrane layer, thereby improving The bursting strength is improved, and the modified hydrolysis aid is fixed inside the hierarchical structure as a cross-linking agent. The hydroxyl groups rich in the surface of the modified titanium dioxide particles on the surface of the modified hydrolysis aid adsorb water molecules, while adjusting the electric field and serving as a hydrolysis reaction center. The multilayer structure of graphene oxide further increases the specific surface area of the hydrolysis functional layer, and increases the contact time and contact area between the modified titanium dioxide particles inside it and the water molecules, thereby enhancing the acid (base) production rate of the bipolar membrane and reducing the transmembrane voltage, and finally obtaining a bipolar membrane with high ion exchange capacity, high bursting strength, low swelling, low transmembrane voltage, acid and alkali resistance and high acid / base production rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0065] Figure 1This is a schematic diagram of the structure of the bipolar membrane prepared by the present invention;
[0066] In the figure: 100, cation exchange membrane; 200, hydrolysis functional layer; 300, anion exchange membrane. DETAILED DESCRIPTION
[0067] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0068] Example 1
[0069] This embodiment is used to provide a bipolar membrane electrodialysis membrane stack and a method for using the same, comprising the following steps:
[0070] S1. Preparation of cation exchange membrane
[0071] Weigh: 6.0 g of polyvinyl chloride powder, 9.0 mL of 20 wt% potassium peroxide solution and 6.0 mL of ethanol, add them into a reactor and stir at a stirring rate of 120 rpm. The temperature of the reactor is raised to 60° C. and stirred for 1 hour. After the temperature of the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80° C. and distilled under reduced pressure until no liquid is produced to obtain activated polyvinyl chloride;
[0072] Weigh: 12.0 g of activated polyvinyl chloride, 6.0 g of 3-aminopropyltriethoxysilane, 0.6 g of triethylamine, 32.0 mL of N,N-dimethylformamide and 24.0 mL of deionized water into a reactor, stir at room temperature for 1 hour, and after the reactor temperature is cooled to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain ammoniated polyvinyl chloride;
[0073] Weigh: 12.0 g of ammoniated polyvinyl chloride, 5.0 g of perfluorooctane sulfonyl fluoride, 32.0 mL of N,N-dimethylformamide and 24.0 mL of cyclohexane, add them into a reactor and stir at a stirring rate of 120 rpm. The temperature of the reactor is raised to 40°C and kept for reaction for 2 hours. After the temperature of the reactor is cooled to room temperature, the reaction liquid is added into a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain perfluorosulfonated polyvinyl chloride;
[0074] Weigh: 8.0g of perfluorosulfonated polyvinyl chloride, 0.8g of modified nano titanium dioxide particles and 40.0mL of N,N-dimethylformamide, add them into a reactor, mix well and add them into an electrospinning machine. Set the voltage of the electrospinning machine to 20kV, the spinning distance to 20cm, the flow rate to 0.5L / h, and the spinning thickness to 50μm. After the electrospinning is completed, place the material in a drying oven at 80°C for vacuum drying until the material has a constant weight to obtain a cation exchange membrane 100.
[0075] S2. Preparation of anion exchange membrane
[0076] Weigh: 10.0 g N, N, N', N'-tetramethyl-2-butene-1, 4-diamine, 8.0 g isocyanoethyl methacrylate, 5.0 g vinylbenzene, 1.6 g azobisisobutyronitrile and 90.0 mL N, N-dimethylformamide, add to a reactor and stir at a stirring rate of 60 rpm, raise the reactor temperature to 40°C, keep stirring for 1 hour, cool the reactor temperature to room temperature, add the reaction solution to a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain modified polyethylene;
[0077] Weigh: 5.0g modified polypropylene, 0.4g triethylamine and 30.0mL N,N-dimethylformamide, add to the reactor and stir, the reactor temperature is raised to 30°C, the stirring rate is 150rpm, 1.0g methyl chloride is added dropwise during the stirring process, and the dropping operation is maintained for 1h. After the dropping is completed, the stirring rate is reduced to 60rpm, and the heat preservation reaction is continued for 1h. After the reactor temperature is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 50°C, and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain quaternary polyethylene;
[0078] Weigh: 8.0g of quaternized polyethylene, 0.6g of modified nano titanium dioxide particles and 36.0mL of N,N-dimethylformamide, add them into a reactor, mix well, and then add them into an electrospinning machine. Set the voltage of the electrospinning machine to 20kV, the spinning distance to 20cm, the flow rate to 0.5L / h, and the spinning thickness to 50μm. After the electrospinning is completed, place the material in a drying oven at a temperature of 50°C for vacuum drying until the material has a constant weight to obtain an anion exchange layer 300.
[0079] S3. Preparation of bipolar membrane
[0080] Weigh: 8.0 g of nano titanium dioxide particles and 24.0 mL of 20 wt% sodium hydroxide aqueous solution are added to a reactor for ultrasonication at an ultrasonic frequency of 20 kHz. The temperature of the reactor is raised to 60° C. and the ultrasonication is maintained for 1 hour. After the ultrasonication is completed, the material is placed in a drying oven at a temperature of 80° C. and vacuum dried until the material has a constant weight, thereby obtaining modified nano titanium dioxide particles;
[0081] Weigh: 10.0 mL of concentrated sulfuric acid and 2.0 mL of concentrated nitric acid to prepare an acidified solution;
[0082] Weigh: 10.0 g potassium permanganate and 5.0 g sodium persulfate to prepare an oxidant;
[0083] Weigh: 12.0g of multilayer graphene and 36.0mL of ethanol are added to a reactor and stirred at a stirring rate of 60rpm. After stirring at room temperature for 15min, 20.0mL of acidified solution is poured into the reactor, and the temperature of the reactor is raised to 40°C. After acidification for 0.5h, 10.0g of oxidant is added to the reactor, and the mixture is stirred at this temperature for 8h. After the reaction is completed, the material is placed in a drying oven at a temperature of 80°C for vacuum drying until the material has a constant weight, thereby obtaining modified nano titanium dioxide particles;
[0084] Weigh: 8.0 g of modified nano titanium dioxide particles, 0.8 g of triethylamine and 36.0 mL of ethanol, mix them evenly and add them to an atomizer. After atomization operation, spray the generated gas evenly on the surface of 16.0 g of graphene oxide. After spraying, place the material in a drying oven at a temperature of 80° C. for vacuum drying until the material has a constant weight, thereby obtaining a modified hydrolysis aid;
[0085] Weigh: 8.0g of modified hydrolysis aid is dispersed in 40.0mL of 1wt% triethylamine aqueous solution to obtain a dispersion, and the dispersion is spin-coated on one side of the anion exchange membrane 300 using a spin coater, and the spin coating thickness is controlled to be 25μm. Then, the cation exchange membrane 100 is attached to the side of the anion exchange membrane 300 on which the dispersion is spin-coated, and the material is extruded using a hot press, and the pressure of the hot press is controlled to be 5MPa, and the temperature is controlled to be 40°C, and the extrusion is performed for 5min. After the electrospinning is completed, the material is placed in a drying oven at a temperature of 50°C for vacuum drying until the material has a constant weight, to obtain a bipolar membrane.
[0086] S4. Assemble bipolar membrane electrodialysis stack and use
[0087] After the bipolar membrane is assembled into a membrane stack unit, the membrane stack unit is installed in an electrodialysis device, and a sensor is installed in the electrodialysis device;
[0088] During use, strictly control the bipolar membrane feed index and control the Ca content in the feed solution. 2+ Mg 2+ and Zn 2+ The concentration of divalent metal ions is less than 0.5 g / L;
[0089] Use a sensor to monitor the feed pressure of the electrodialysis device and maintain the feed pressure between 0.06MPa;
[0090] Use sensors to monitor the membrane stack voltage and adjust the membrane stack current. When the membrane stack voltage becomes abnormal during the electrolysis process, the operating current of the corresponding membrane stack with abnormal voltage will be temporarily reduced to 10A, and the voltage change trend will be observed. When the voltage stabilizes, the original operating current will be gradually restored.
[0091] Example 2
[0092] This embodiment is used to provide a bipolar membrane electrodialysis membrane stack and a method for using the same, comprising the following steps:
[0093] S1. Preparation of cation exchange membrane
[0094] Weigh: 8.0 g of polyvinyl chloride powder, 8.0 mL of 30 wt% potassium peroxide solution and 4.0 mL of ethanol, add them into a reactor and stir at a stirring rate of 120 rpm, raise the temperature of the reactor to 80° C., keep warm and stir for 2 hours, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 100° C., and distill under reduced pressure until no liquid is produced to obtain activated polyvinyl chloride;
[0095] Weigh: 16.0 g of activated polyvinyl chloride, 6.0 g of 3-aminopropyltriethoxysilane, 0.8 g of triethylamine, 40.0 mL of N,N-dimethylformamide and 24.0 mL of deionized water into a reactor, stir at room temperature for 2 h, and after the reactor temperature is cooled to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 100° C., and distill under reduced pressure until no liquid is produced to obtain ammoniated polyvinyl chloride;
[0096] Weigh: 16.0g of ammoniated polyvinyl chloride, 5.0g of perfluorooctane sulfonyl fluoride, 36.0mL of N,N-dimethylformamide and 24.0mL of cyclohexane are added to a reactor and stirred at a stirring rate of 120rpm. The temperature of the reactor is raised to 60°C and the reaction is kept warm for 3h. After the temperature of the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C, and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain perfluorosulfonated polyvinyl chloride;
[0097] Weigh: 8.0 g of perfluorosulfonated polyvinyl chloride, 0.6 g of modified nano titanium dioxide particles and 40.0 mL of N,N-dimethylformamide, add them into a reactor, mix well, and then add them into an electrospinning machine. Set the voltage of the electrospinning machine to 25 kV, the spinning distance to 30 cm, the flow rate to 1 L / h, and the spinning thickness to 100 μm. After the electrospinning is completed, place the material in a drying oven at 80°C for vacuum drying until the material has a constant weight to obtain a cation exchange membrane 100.
[0098] S2. Preparation of anion exchange membrane
[0099] Weigh: 12.0 g N, N, N', N'-tetramethyl-2-butene-1, 4-diamine, 8.0 g isocyanoethyl methacrylate, 5.0 g vinylbenzene, 2.0 g azobisisobutyronitrile and 90.0 mL N, N-dimethylformamide, add to a reactor and stir at a stirring rate of 80 rpm, raise the reactor temperature to 60°C, keep stirring for 2 hours, cool the reactor temperature to room temperature, add the reaction solution to a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain modified polyethylene;
[0100] Weigh: 5.0g modified polypropylene, 0.2g triethylamine and 30.0mL N,N-dimethylformamide, add to the reactor and stir, the reactor temperature is raised to 50°C, the stirring rate is 180rpm, 0.8g methyl chloride is added dropwise during the stirring process, and the dropping operation is maintained for 3h. After the dropping is completed, the stirring rate is reduced to 80rpm, and the heat preservation reaction is continued for 2h. After the reactor temperature is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 50°C, and the reduced pressure distillation is carried out until no liquid is produced to obtain quaternary polyethylene;
[0101] Weigh: 8.0g of quaternized polyethylene, 0.8g of modified nano titanium dioxide particles and 40.0mL of N,N-dimethylformamide, add them into a reactor, mix well, and then add them into an electrospinning machine. Set the voltage of the electrospinning machine to 25kV, the spinning distance to 30cm, the flow rate to 1L / h, and the spinning thickness to 100μm. After the electrospinning is completed, place the material in a drying oven at 50°C for vacuum drying until the material has a constant weight to obtain an anion exchange layer 300.
[0102] S3. Preparation of bipolar membrane
[0103] Weigh: 10.0 g of nano titanium dioxide particles and 24.0 mL of 30 wt% sodium hydroxide aqueous solution are added to a reactor for ultrasonication at an ultrasonic frequency of 40 kHz. The temperature of the reactor is raised to 80° C. and the ultrasonication is maintained for 2 h. After the ultrasonication is completed, the material is placed in a drying oven at a temperature of 80° C. for vacuum drying until the material has a constant weight, thereby obtaining modified nano titanium dioxide particles;
[0104] Weigh: 10.0 mL of concentrated sulfuric acid and 2.0 mL of concentrated nitric acid to prepare an acidified solution;
[0105] Weigh: 10.0 g potassium permanganate and 5.0 g sodium persulfate to prepare an oxidant;
[0106] Weigh: 12.0g of multilayer graphene and 36.0mL of ethanol are added to a reactor and stirred at a stirring rate of 80rpm. After stirring at room temperature for 20min, 120.0mL of acidified solution is poured into the reactor, and the temperature of the reactor is raised to 60°C. After acidification for 0.5h, 8.0g of oxidant is added to the reactor, and the mixture is stirred at this temperature for 12h. After the reaction is completed, the material is placed in a drying oven at 80°C for vacuum drying until the material has a constant weight, thereby obtaining modified nano titanium dioxide particles;
[0107] Weigh: 10.0 g of modified nano titanium dioxide particles, 0.8 g of triethylamine and 36.0 mL of ethanol, mix them evenly and add them to an atomizer. After atomization operation, spray the generated gas evenly on the surface of 18.0 g of graphene oxide. After spraying, place the material in a drying oven at a temperature of 80° C. for vacuum drying until the material has a constant weight, thereby obtaining a modified hydrolysis aid;
[0108] Weigh: 8.0g of modified hydrolysis aid is dispersed in 40.0mL of 3wt% triethylamine aqueous solution to obtain a dispersion, and the dispersion is spin-coated on one side of the anion exchange membrane 300 using a spin coater, and the spin coating thickness is controlled to be 50μm. Then, the cation exchange membrane 100 is attached to the side of the anion exchange membrane 300 on which the dispersion is spin-coated, and the material is extruded using a hot press, and the pressure of the hot press is controlled to be 8MPa, and the temperature is controlled to be 60°C, and the extrusion is performed for 10min. After the electrospinning is completed, the material is placed in a drying oven at a temperature of 50°C for vacuum drying until the material has a constant weight, to obtain a bipolar membrane.
[0109] S4. Assemble bipolar membrane electrodialysis stack and use
[0110] After the bipolar membrane is assembled into a membrane stack unit, the membrane stack unit is installed in an electrodialysis device, and a sensor is installed in the electrodialysis device;
[0111] During use, strictly control the bipolar membrane feed index and control the Ca content in the feed solution. 2+ Mg 2+ and Zn 2+ The concentration of divalent metal ions is less than 0.5 g / L;
[0112] Use a sensor to monitor the feed pressure of the electrodialysis device and maintain the feed pressure between 0.09MPa;
[0113] Use sensors to monitor the membrane stack voltage and adjust the membrane stack current. When the membrane stack voltage becomes abnormal during the electrolysis process, the operating current of the corresponding membrane stack with abnormal voltage will be temporarily reduced to 50A, and the voltage change trend will be observed. When the voltage stabilizes, the original operating current will be gradually restored.
[0114] Example 3
[0115] This embodiment is used to provide a bipolar membrane electrodialysis membrane stack and a method for using the same, comprising the following steps:
[0116] S1. Preparation of cation exchange membrane
[0117] Weigh: 6.0 g of polyvinyl chloride powder, 9.0 mL of 25 wt% potassium peroxide solution and 6.0 mL of ethanol, add them into a reactor and stir at a stirring rate of 120 rpm. The temperature of the reactor is raised to 70° C. and stirred for 2 h. After the temperature of the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 90° C. and distilled under reduced pressure until no liquid is produced to obtain activated polyvinyl chloride;
[0118] Weigh: 16.0 g of activated polyvinyl chloride, 4.0 g of 3-aminopropyltriethoxysilane, 0.8 g of triethylamine, 36.0 mL of N,N-dimethylformamide and 30.0 mL of deionized water into a reactor, stir at room temperature for 2 h, and after the reactor temperature is cooled to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 90° C., and distill under reduced pressure until no liquid is produced to obtain ammoniated polyvinyl chloride;
[0119] Weigh: 16.0 g of ammoniated polyvinyl chloride, 6.0 g of perfluorooctane sulfonyl fluoride, 32.0 mL of N,N-dimethylformamide and 30.0 mL of cyclohexane, add them into a reactor and stir at a stirring rate of 120 rpm, raise the temperature of the reactor by 50°C, and keep the temperature for reaction for 3 hours. After the reactor temperature is cooled to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 90°C, and distill under reduced pressure until no liquid is produced to obtain perfluorosulfonated polyvinyl chloride;
[0120] Weigh: 10.0g perfluorosulfonated polyvinyl chloride, 0.8g modified nano titanium dioxide particles and 40.0mL N,N-dimethylformamide, add into the reactor, mix well and add into the electrospinning machine, set the voltage of the electrospinning machine to 24kV, the spinning distance to 24cm, the flow rate to 0.8L / h, the spinning thickness to 75μm, after the electrospinning is completed, place the material in a drying oven at 80°C for vacuum drying until the material has a constant weight, to obtain a cation exchange membrane 100.
[0121] S2. Preparation of anion exchange membrane
[0122] Weigh: 12.0 g N, N, N', N'-tetramethyl-2-butene-1, 4-diamine, 8.0 g isocyanoethyl methacrylate, 6.0 g vinylbenzene, 2.0 g azobisisobutyronitrile and 90.0 mL N, N-dimethylformamide, add to a reactor and stir at a stirring rate of 70 rpm, raise the reactor temperature to 50°C, keep stirring for 2 hours, cool the reactor temperature to room temperature, add the reaction solution to a rotary evaporator with a water bath temperature of 90°C, and distill under reduced pressure until no liquid is produced to obtain modified polyethylene;
[0123] Weigh: 6.0g modified polypropylene, 0.2g triethylamine and 30.0mL N,N-dimethylformamide are added to a reactor and stirred. The temperature of the reactor is raised to 40°C and the stirring rate is 160rpm. During the stirring process, 0.8g methyl chloride is added dropwise. The dropping operation is maintained for 1-3h. After the dropping is completed, the stirring rate is reduced to 70rpm. The heat preservation reaction is continued for 2h. After the temperature of the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 50°C, and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain quaternary polyethylene;
[0124] Weigh: 10.0g of quaternized polyethylene, 0.8g of modified nano titanium dioxide particles and 40.0mL of N,N-dimethylformamide, add them into a reactor, mix well and add them into an electrospinning machine, set the voltage of the electrospinning machine to 24kV, set the spinning distance to 25cm, control the flow rate at 0.8L / h, and the spinning thickness to 75μm. After the electrospinning is completed, place the material in a drying oven at 50°C for vacuum drying until the material has a constant weight to obtain an anion exchange layer 300.
[0125] S3. Preparation of bipolar membrane
[0126] Weigh: 8.0 g of nano titanium dioxide particles and 24.0 mL of 25 wt% sodium hydroxide aqueous solution are added to a reactor for ultrasonication at an ultrasonic frequency of 30 kHz. The temperature of the reactor is raised to 70° C. and the ultrasonication is maintained for 2 h. After the ultrasonication is completed, the material is placed in a drying oven at a temperature of 80° C. and vacuum dried until the material has a constant weight, thereby obtaining modified nano titanium dioxide particles;
[0127] Weigh: 10.0 mL of concentrated sulfuric acid and 2.0 mL of concentrated nitric acid to prepare an acidified solution;
[0128] Weigh: 10.0 g potassium permanganate and 5.0 g sodium persulfate to prepare an oxidant;
[0129] Weigh: 16.0g of multilayer graphene and 40.0mL of ethanol are added to a reactor and stirred at a stirring rate of 70rpm. After stirring at room temperature for 18min, 20.0mL of acidified solution is poured into the reactor, and the temperature of the reactor is raised to 50°C. After acidification for 0.5h, 8.0g of oxidant is added to the reactor, and the reaction is stirred for 10h. After the reaction is completed, the material is placed in a drying oven at a temperature of 80°C for vacuum drying until the material is constant weight, to obtain modified nano titanium dioxide particles;
[0130] Weigh: 8.0 g of modified nano titanium dioxide particles, 1.0 g of triethylamine and 40.0 mL of ethanol, mix them evenly and add them to an atomizer. After atomization operation, spray the generated gas evenly on the surface of 18.0 g of graphene oxide. After spraying, place the material in a drying oven at a temperature of 80° C. and vacuum dry it until the material has a constant weight to obtain a modified hydrolysis aid.
[0131] Weigh: 8.0 g of modified hydrolysis aid is dispersed in 48.0 mL of 2 wt% triethylamine aqueous solution to obtain a dispersion, and the dispersion is spin-coated on one side of the anion exchange membrane 300 using a spin coater, and the spin coating thickness is controlled to be 36 μm. The cation exchange membrane 100 is then attached to the side of the anion exchange membrane 300 on which the dispersion is spin-coated, and the material is extruded using a hot press, and the pressure of the hot press is controlled to be 6 MPa, and the temperature is 50°C, and the extrusion is performed for 8 minutes. After the electrospinning is completed, the material is placed in a drying oven at a temperature of 50°C for vacuum drying until the material has a constant weight, to obtain a bipolar membrane.
[0132] S4. Assemble bipolar membrane electrodialysis stack and use
[0133] After the bipolar membrane is assembled into a membrane stack unit, the membrane stack unit is installed in an electrodialysis device, and a sensor is installed in the electrodialysis device;
[0134] During use, strictly control the bipolar membrane feed index and control the Ca content in the feed solution. 2+ Mg 2+ and Zn 2+ The concentration of divalent metal ions is less than 0.5 g / L;
[0135] Use a sensor to monitor the feed pressure of the electrodialysis device and maintain the feed pressure between 0.08MPa;
[0136] Use sensors to monitor the membrane stack voltage and adjust the membrane stack current. When the membrane stack voltage becomes abnormal during the electrolysis process, the operating current of the corresponding membrane stack with abnormal voltage will be temporarily reduced to 30A, and the voltage change trend will be observed. When the voltage stabilizes, the original operating current will be gradually restored.
[0137] Comparative Example 1
[0138] The difference between this comparative example and Example 3 is that step S1 is eliminated, and in step S3, an equal amount of sulfonated polystyrene cation exchange membrane is used to replace the cation exchange membrane.
[0139] Comparative Example 2
[0140] The difference between this comparative example and Example 3 is that step S2 is eliminated, and in step S3, an equal amount of quaternized polyvinylidene chloride anion exchange membrane is used to replace the anion exchange membrane.
[0141] Comparative Example 3
[0142] The difference between this comparative example and Example 3 is that the step of activating the nano titanium dioxide particles in step S3 is eliminated, and an equal amount of nano titanium dioxide particles is used to replace the modified nano titanium dioxide particles.
[0143] Comparative Example 4
[0144] The difference between this comparative example and Example 3 is that the step of oxidizing multilayer graphene in step S3 is eliminated, and an equal amount of modified nano titanium dioxide particles is used to replace the modified hydrolysis aid.
[0145] Performance Testing:
[0146] The ion exchange capacity, burst strength, dimensional change rate, transmembrane voltage, chemical tolerance and acid / base production rate of the bipolar membranes prepared in Examples 1-3 and Comparative Examples 1-4 were tested with reference to the standard HG / T 6093-2022 "Bipolar Membranes". The specific data are shown in Table 1.
[0147] Three bipolar membranes prepared in Example 3 were taken and respectively loaded into electrolytic cells with feed pressures of 0.06 MPa, 0.09 MPa and 0.12 MPa. The calcium and magnesium contents in the feed solution used in the electrolytic cells were 0.3 mg / L, 0.5 mg / L and 3 mg / L, respectively. The three electrolytic cells were numbered electrolytic cells 1-3. During the electrolysis process, the change of membrane voltage was monitored in real time. If a significant change was found, the current was adjusted to 30.0 A until the current returned to normal after the fault was eliminated. The service life of the bipolar membrane electrodialysis membrane stack was tested by the above method. The specific data are shown in Table 2.
[0148] Table 1-Performance test data of each sample
[0149]
[0150]
[0151] Table 2 - Statistics of bipolar membrane service life
[0152]
[0153] Data Analysis:
[0154] By analyzing the data in Table 1 and Table 2, it can be found that the ion exchange capacity of the ion exchanger prepared by the present invention reaches 0.8 mol·kg -1 , burst strength of 0.35 MPa, dimensional change rate of 6%, transmembrane voltage of 1.3 V, chemical resistance (burst strength decrease rate) of 7% and acid (base) production rate of 0.21 mol·(m 2 ·min), and the service life of the bipolar membrane stack assembled with the bipolar membrane prepared by the present invention is extended by 10 months by the method for extending the service life of the bipolar membrane electrodialysis stack used in the present invention, and various performance test data are better than those of the comparative example;
[0155] The cation exchange membrane prepared by the present invention attracts cations through a large number of sulfonic acid groups on its surface, effectively attracts and transmits positively charged ions through the membrane, and the anion exchange membrane attracts and transmits positively charged ions through a large number of quaternary ammonium salt groups on its surface, thereby improving the ion exchange capacity of the bipolar membrane and reducing the transmembrane voltage. The large number of fluorine groups and tertiary amine structures respectively present in the molecular chain further improve the acid and alkali resistance and anti-swelling performance of the two. The modified nano-silica particles inside the two provide a skeleton structure for the membrane layer, improve the burst strength, and act as a cross-linking agent. The modified hydrolysis aid is fixed inside the hierarchical structure, and the hydroxyl groups rich in the surface of the modified titanium dioxide particles on the surface of the modified hydrolysis aid adsorb water molecules, and at the same time adjust the electric field and serve as a hydrolysis reaction center. The multilayer structure of graphene oxide further increases the specific surface area of the hydrolysis functional layer, and increases the contact time and contact area between the modified titanium dioxide particles inside it and the water molecules, thereby enhancing the acid (base) production rate of the bipolar membrane and reducing the transmembrane voltage, and finally obtaining a bipolar membrane with high ion exchange capacity, high burst strength, low swelling, low transmembrane voltage, acid and alkali resistance, and high acid / base production rate;
[0156] The invention discloses a method for using a bipolar membrane electrodialysis membrane stack provided by the present invention. By regulating the composition of the feed liquid, the adhesion of divalent ions to the membrane surface is reduced, the process of membrane blockage and calcification is slowed down, and the life of the membrane is greatly improved. By regulating the pressure of the feed liquid, the negative impact of membrane stack diaphragm bulging caused by excessive feed liquid pressure, which in turn causes leakage, is reduced. At the same time, insufficient feed volume due to too low pressure will not be caused, which will lead to pressure imbalance in the acid-base salt chamber and membrane burning due to lack of material. By real-time detection of the membrane stack voltage and adjustment of the bipolar membrane operating current, the ion separation efficiency in the bipolar membrane is reduced due to voltage and current mismatch, which leads to ion accumulation or initiation of side reactions, such as gas precipitation on the electrode surface, and the adverse effects of such side reactions on the material and performance of the membrane are reduced, the membrane structure is protected, and the degradation of the membrane material is delayed. At the same time, the bipolar membrane is very sensitive to the transmembrane voltage (membrane stack voltage). When the voltage is abnormal, it will cause local overheating, mechanical damage and chemical degradation of the membrane, thereby reducing the service life of the membrane.
[0157] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0158] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0159] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A bipolar membrane electrodialysis membrane stack, characterized in that: It includes an anode plate, a plurality of membrane stack units, a cathode plate and a pressing plate for fixing the membrane stack, wherein the membrane stack unit is sequentially provided with a cation exchange membrane, a bipolar membrane and an anion exchange membrane; The bipolar membrane comprises a cation exchange membrane (100), an anion exchange membrane (300) and a hydrolysis functional layer (200); The cation exchange membrane (100) is prepared from perfluorosulfonated polyvinyl chloride, the anion exchange membrane (100) is prepared from quaternized polyethylene, and the hydrolysis functional layer (200) is composed of a modified hydrolysis aid prepared from modified graphene.
2. A bipolar membrane electrodialysis membrane stack according to claim 1, characterized in that: The preparation method of the perfluorosulfonated polyvinyl chloride comprises the following steps: A1. Add polyvinyl chloride powder, 20-30wt% potassium peroxide solution and ethanol into a reactor and stir. Raise the temperature of the reactor to 60-80°C, keep warm and stir for 1-2h, and perform post-treatment to obtain activated polyvinyl chloride. A2, adding activated polyvinyl chloride, 3-aminopropyltriethoxysilane, triethylamine, N,N-dimethylformamide and deionized water into a reaction kettle, stirring at room temperature for 1-2 hours, and post-treating to obtain aminated polyvinyl chloride; A3. Add ammoniated polyvinyl chloride, perfluorooctane sulfonyl fluoride, N,N-dimethylformamide and cyclohexane into a reaction kettle and stir. The temperature of the reaction kettle is increased to 40-60°C. The reaction is kept warm for 2-3 hours. After post-treatment, perfluorosulfonated polyvinyl chloride is obtained.
3. A bipolar membrane electrodialysis membrane stack according to claim 1, characterized in that: The preparation method of the quaternized polyethylene comprises the following steps: B1. Add N,N,N',N'-tetramethyl-2-butene-1,4-diamine, isocyanoethyl methacrylate, vinylbenzene, azobisisobutyronitrile and N,N-dimethylformamide into a reaction kettle and stir. The temperature of the reaction kettle is raised to 40-60°C, and the mixture is stirred for 1-2 hours at the same temperature. The modified polyethylene is obtained by post-treatment. B2. Add modified polypropylene, triethylamine and N,N-dimethylformamide into a reactor and stir. The temperature of the reactor is raised to 30-50°C and the stirring rate is 150-180rpm. Methyl chloride is added dropwise during stirring. The dropping operation is maintained for 1-3h. After the dropping is completed, the stirring rate is reduced to 60-80rpm. The reaction is kept warm for 1-2h and the quaternized polyethylene is obtained by post-treatment.
4. The bipolar membrane electrodialysis stack according to claim 1, characterized in that: The preparation method of the modified hydrolysis aid comprises the following steps: C1, adding nano titanium dioxide particles and 20-30wt% sodium hydroxide aqueous solution into a reaction kettle for ultrasonication, raising the temperature of the reaction kettle to 60-80°C, maintaining the temperature for 1-2h, and post-treating to obtain modified nano titanium dioxide particles; C2, adding multilayer graphene and ethanol to a reactor and stirring, stirring at room temperature for 15-20 minutes, pouring the acidified solution into the reactor, and raising the temperature of the reactor to 40-60°C, after acidification for 0.5 hours, adding an oxidant to the reactor, keeping warm and stirring for 8-12 hours, and post-treating to obtain graphene oxide; C3. The modified nano titanium dioxide particles, triethylamine and ethanol are mixed evenly and added into an atomizer. After atomization operation, the generated gas is evenly sprayed on the surface of graphene oxide, and a modified hydrolysis aid is obtained by post-treatment.
5. The bipolar membrane electrodialysis stack according to claim 1, characterized in that: The preparation method of the bipolar membrane is: D1, adding perfluorosulfonated polyvinyl chloride, modified nano titanium dioxide particles and N,N-dimethylformamide into a reaction kettle, mixing them evenly, and then adding them into an electrospinning machine for electrospinning, and post-treating to obtain a cation exchange membrane (100); D2, adding quaternized polyethylene, modified nano titanium dioxide particles and N,N-dimethylformamide into a reaction kettle, mixing evenly, and then adding into an electrospinning machine for electrospinning, and post-processing to obtain an anion exchange membrane (300); D3. Disperse the modified hydrolysis aid in a 1-3wt% triethylamine aqueous solution to obtain a dispersion, and use a spin coater to spin-coat the dispersion on one side of the anion exchange membrane (300), controlling the spin coating thickness to be 25-50μm, and then attaching the cation exchange membrane (100) to the side of the anion exchange membrane (300) on which the dispersion is spin-coated, and use a hot press to extrude the material, and post-process to obtain a bipolar membrane.
6. A method for using a bipolar membrane electrodialysis stack according to any one of claims 1 to 5, characterized in that: Includes the following methods: S1. After assembling the bipolar membrane into a membrane stack unit, the membrane stack unit is installed in an electrodialysis device, and a sensor is installed in the electrodialysis device; S2. Treat the liquid composition before feeding the electrodialysis device to control the Ca content in the liquid 2+ Mg 2+ and Zn 2+ The concentration of divalent metal ions is less than 0.5 g / L; S3, stabilize the feed pressure during feeding, and maintain the feed pressure between 0.06-0.09MPa; S4. Adjust the membrane stack current during the electrolysis process and detect the membrane stack voltage during the electrolysis process. When the voltage is abnormal, temporarily reduce the operating current of the membrane stack corresponding to the abnormal voltage to 10-50A, observe the voltage change trend, and gradually restore the original operating current when the voltage stabilizes.
Citation Information
Patent Citations
Electrodialyzer
CN109012201A
Bipolar membrane and preparation method thereof
CN112546873A